Synaptic Wnt/GSK3β Signaling Hub in Autism - Mario O. Caracci; Miguel E. Ávila; Giancarlo V. De Ferrari (Neural Plasticity)
Hundreds of genes have been associated with autism spectrum disorders (ASDs) and the interaction of weak and de novo variants derive from distinct autistic phenotypes thus making up the “spectrum.” The convergence of these variants in networks of genes associated with synaptic function warrants the study of cell signaling pathways involved in the regulation of the synapse. The Wnt/β-catenin signaling pathway plays a central role in the development and regulation of the central nervous system and several genes belonging to the cascade have been genetically associated with ASDs. In the present paper, we review basic information regarding the role of Wnt/β-catenin signaling in excitatory/inhibitory balance (E/I balance) through the regulation of pre- and postsynaptic compartments. Furthermore, we integrate information supporting the role of the glycogen synthase kinase 3β (GSK3β) in the onset/development of ASDs through direct modulation of Wnt/β-catenin signaling. Finally, given GSK3β activity as key modulator of synaptic plasticity, we explore the potential of this kinase as a therapeutic target for ASD.